2014
DOI: 10.1186/1746-160x-10-5
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam computed tomographic evaluation of styloid process: a retrospective study of 208 patients with orofacial pain

Abstract: IntroductionThe purpose of this study was to assess the structural characteristics of styloid process (SP) by cone-beam computed tomography (CBCT) examination in a patient population suffering from orofacial pain. The second aim was to assess the prevalence of elongated SP and its relation to gender, site and subjective symptoms in the study population.MethodsClinical and radiographic records of 208 patients were evaluated retrospectively. Radiological examinations including measurements of the structure, leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 20 publications
7
38
0
10
Order By: Relevance
“…Stylopharyngeus, stylohyoid, styloglossus muscles, stylohyoid and stylomandibular ligaments are attached to the styloid process 2. The length of the styloid process is reported to range between 15.2 mm and 47.7 mm,3 and various authors have observed that the normal length of the styloid process is between 20 mm and 30 mm,39 with length >30 mm regarded as elongated 24,713. This elongation of the styloid process or calcification of ligaments, which is the cause of the stylohyoid syndrome or Eagle syndrome, was first reported by the otorhinolaryngologist Eagle 14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stylopharyngeus, stylohyoid, styloglossus muscles, stylohyoid and stylomandibular ligaments are attached to the styloid process 2. The length of the styloid process is reported to range between 15.2 mm and 47.7 mm,3 and various authors have observed that the normal length of the styloid process is between 20 mm and 30 mm,39 with length >30 mm regarded as elongated 24,713. This elongation of the styloid process or calcification of ligaments, which is the cause of the stylohyoid syndrome or Eagle syndrome, was first reported by the otorhinolaryngologist Eagle 14…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of the elongation of the styloid process is not yet exactly determined, but the congenital elongation of the styloid process, calcification of the stylohyoid ligament and growth of osseous tissue where the stylohyoid ligament inserts are regarded as few of the causative factors 16,17. Radiographic studies report the prevalence of the elongated styloid process from 2% to 30% 2,6,9,18,19. Elongation may be seen in both sexes, unilaterally or bilaterally and more commonly in elderly individuals 15.…”
Section: Introductionmentioning
confidence: 99%
“…Eagle sendromu SP'in uzaması, deforme olması veya styloid ligamentin kalsifiye olması sonucu oluşan bir hastalıktır [7][8][9][10][11] .…”
Section: Materyal Ve Methodsunclassified
“…Eagle sendromu SP'in uzaması, deforme olması veya styloid ligamentin kalsifiye olması sonucu oluşan bir hastalıktır [7][8][9][10][11] . Boğaz ağrısı, kulak ağrısı, ses değişikliği, baş boyun ağrıları, Eagle sendromunun en çok görülen belirtileridir 12,13 .…”
Section: Tartiġmaunclassified